Dendrimers: Potential Drug Carrier For Novel Drug Delivery System - Kumar, Inder; Dhiman, Sunny; Palia, Priyankul; Kumar, Pankaj; Sharma, Nishant (Asian Journal of Pharmaceutical Research and Development, 2021)
Dendrimers are new effectiveness of polymeric substances. They are relatively branched, monodisperse macromolecules. Structural Advantages permit dendrimers to play a critical function inside the fields of nanotechnology, pharmaceutical, and medicinal chemistry. As a result in their precise behavior dendrimers are suitable for a wide variety of biomedical and commercial packages. The paper gives a quick evaluation of dendrimers’ physicochemical properties and their possible use in various regions of research, generation, and treatment.